Association between monocyte-to-HDL ratio and Fazekas-scaled white matter hyperintensities in migraine patients: a cross-sectional MRI-based study - Yıldoğan, Aydın Talip; Şencan, Ramazan; Yıldoğan, Gizem Türker; Öngün, Gözde; Ulusoy, Bekir Sıtkı Said; Eren, Fettah; Neyal, Abdurrahman (Frontiers in Neurology, 2025)
BackgroundThis study aimed to investigate the association between the monocyte-to-high density lipoprotein (HDL) cholesterol ratio (MHR) and the presence and severity of white matter hyperintensities (WMHs) in patients with migraine.MethodsA total of 153 patients diagnosed with migraine and 90 age- and sex-matched healthy controls were included. Serum monocyte and HDL levels, and MRI findings were evaluated. WMHs severity was graded using the Fazekas scale. Serum parameters were compared and evaluated between the patient and control groups. In addition, the relationship between migraine clinical characteristics and MHR levels was examined.ResultsMHR values were significantly higher in migraine patients than in controls (p < 0.001). Higher Fazekas scores were associated with increased MHR and monocyte levels, and decreased HDL levels. Receiver operating characteristic (ROC) analysis indicated that an MHR > 13.37 predicted the presence of WMHs with 88.50% sensitivity and 98% specificity (AUC = 0.918, p < 0.001).ConclusionMHR appears to be a promising inflammatory biomarker reflecting cerebral microvascular changes in migraine patients, even among young adults. These results support the contribution of low-grade systemic inflammation to migraine-associated white matter lesions.